Proceedings of the 2011 Winter Simulation Conference (WSC) 2011
DOI: 10.1109/wsc.2011.6147841
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based modeling framework to deal with Clinical Pathways

Abstract: In this paper we focus our attention on the analysis and management of Clinical Pathways (CPs) in health care systems. From an operational point of view, the CP is "the path" followed by a patient with a given pathology through the health-care system. We start by a global vision and propose a modeling framework based on a discrete event simulation model to identify the critical activities and scarce resources that represent the process bottlenecks both from a patient-centered and facility-centered point of vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Obtained Data Driven [5, 7-9, 11, 13, 32, 33, 37, 47-49, 54, 58, 62, 66, 70-72, 74-76, 80, 81, 83, 85-99, 104, 107, 108, 112, 120, 121, 124, 126, 127, 131, 133, 134, 138-140, 143, 144, 147-150, 153, 157, 160, 162, 167, 170, 172, 177-179, 183-185, 191, 192, 195, 197-206, 209-211] Collaboration [3,10,14,17,27,42,51,73,100,114,142,152,163] Both [12,20,35,40,56,101,103,129,136,146,154,166,171,186] Other [19,21,22,24,41,60,79,82,116,128,169] Table A6. Care level considered.…”
Section: Fundingmentioning
confidence: 99%
“…Obtained Data Driven [5, 7-9, 11, 13, 32, 33, 37, 47-49, 54, 58, 62, 66, 70-72, 74-76, 80, 81, 83, 85-99, 104, 107, 108, 112, 120, 121, 124, 126, 127, 131, 133, 134, 138-140, 143, 144, 147-150, 153, 157, 160, 162, 167, 170, 172, 177-179, 183-185, 191, 192, 195, 197-206, 209-211] Collaboration [3,10,14,17,27,42,51,73,100,114,142,152,163] Both [12,20,35,40,56,101,103,129,136,146,154,166,171,186] Other [19,21,22,24,41,60,79,82,116,128,169] Table A6. Care level considered.…”
Section: Fundingmentioning
confidence: 99%
“…Given the parameters presented in Tables 2 and 3, we will deploy simulation-optimization approach as a main component of a more comprehensive performance assessment and management framework for analyzing clinical pathways [33,34]. In this study, we apply the simulation-optimization approach to model a real case, namely to evaluate the thyroid surgical treatment together with the other surgery-based CPs.…”
Section: Simulation-optimization Modelling Approachmentioning
confidence: 99%
“…In Section 3.1, the prototype simulation model proposed in Ozcan et al [33] has been revised and fine-tuned to represent the operative scenario of the Department under study and the observed patient flows. In Section 3.2, the model has been fine-tuned and validated with the new data collected in the present case study.…”
Section: Simulation-optimization Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Because all practical aspects of the hospital cannot be simulated, it is important to incorporate institutional knowledge at the highest possible level to decide what aspects to include in the development of the simulation model. 32,33 The goal was to understand the magnitude of change that could be expected if these scenarios were implemented in the actual hospital. The model was constructed using the Promodel simulation software.…”
Section: Validation Using Simulationmentioning
confidence: 99%